Development of National Sociologies in Central and Eastern Europe - Miltojević, Vesna D. (Sociološki pregled, 2019)
The specifc socio-economic and political situation in Central and Eastern European countries undoubtedly contributed to the fact that sociology, as a scientifc and academic discipline, constituted there rather late compared to other parts of the world. However, this is not a reason not to mention numerous social thinkers from this region, other than those who emigrated, in the reviews of the history of social thought. The translation of the History of Sociological Tought in the Central and Eastern European Countries written by Zinaida T. Golenkova and Nikolai P. Narbut is a great opportunity, not only for Russian but also for Serbian students, to familiarize themselves with the forerunners of sociology, well-known sociologists and the most signifcant research problems in the Central and Eastern European region.
Keywords: Central and Eastern Europe; sociologists’ research areas; constitution of sociology; institutionalization of sociology; education of students